Mappare la distruzione: locative media e narrazione del sisma ad Amatrice - Marta Milia (Ocula, 2019)
This contribution intends to analyze the relationship between the practice of geolocation, through mobile devices and social media, and the management of events having a particularly traumatic impact on a community. The study concerns the earthquake that struck central Italy on August 2016 and in particular the town of Amatrice, with a focus on the narration and localization of the daily activities of individuals. The reflection on the relationship between locative Media and the narration of everyday life, of the experience through the space-based location and of the destruction not only of physical but also of metaphorical places, is articulated through the study and monitoring of such "sense mappings" on social media. They are well recognizable and distinguishable through markers proper of their diffusion, such as the hashtags. Such individual narrative process becomes "usable" by other individuals through the so-called Locative Media, which allow to share not only a geographical position accompanied by images, phrases, videos, but also the personal and intimate experiences which evolve into visible, analyzable and public narratives, that can be shared by other users.